Preparticipation examination (screening): Practical issues as determined by sport: A United Kingdom perspective - Batt, M. E.; Jaques, R.; Stone, M. (Clinical Journal of Sport Medicine, 2004)
Objectives: Pre-participation examination, screening and health surveillance are part of the job specification for many roles within Sports Medicine. The type and scope of this activity varies enormously, with little consensus as to best evidence-based practice. The purpose of this work was to explore and understand the practical approaches to pre-participation examination, screening and health surveillance in two contrasting sport scenarios. Data Source: Team physicians for British Triathlon and Manchester United Football Club. Data synthesis/Methods: Information was gathered under the headings: why screen, screening objectives, practical issues and constraints? Results: The systems evolved within these two sports reflect their respective opportunities and constraints. Different systems, each with merit, have evolved with some generalizable concepts across sport. Conclusions: A perfect system for pre-participation examination, screening and health surveillance across all sport does not exist, however, within specific sport scenarios examples of good practice are demonstrated.